Development and evaluation of a code frame to identify potential primary care presentations in the hospital emergency department. (2nd May 2019) - Schütze, Heike; Rees, Rhyannan; Asha, Stephen; Eagar, Kathy
Abstract: Objective: A major challenge in evaluating the appropriateness of ED presentations is the lack of a universal and workable definition of patients who could have received primary care instead. Our objective was to develop a standardised code frame to identify potential primary care patients in the ED. Methods: A standardised code frame to identify which patients could potentially be treated in a primary care setting was developed and tested on all patient episodes of care who presented to the ED of the St George Hospital, Sydney, between December 2016 and February 2017. Sensitivity and specificity of the code frame were performed. The code frame was then tested on all presentations from 2011 to 2016 in the St George Hospital and The Sutherland Hospital in Sydney. Results: Of 19 916 ED presentations, 5810 (29%) were potential primary care presentations. The code frame had a sensitivity of 99.9% and a specificity of 49.0%. Results were consistent (28%) when applied to 5 years of presentations (601 168 presentations). Conclusion: This standardised code frame enables accurate retrospective local and national data estimations. The code frame could be used prospectively to evaluate interventions such as diverting patients to primary care settings, and to identify populations for specifically targeted interventions. The conservative nature of the code frame ensures that only those that can safely receive care in a primary care setting are identified as potential primary care.